(untitled) (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Congenital anomalies of the kidney and urinary tract (CAKUT) are a leading cause of chronic kidney disease, but data on their prevalence and patterns in Bangladesh is limited. This study aimed to address this gap by characterizing CAKUT in a local population. Methods: This was a hospital-based cross-sectional study conducted over one year at a tertiary hospital. A total of 100 patients (infants, children, and adults) with confirmed CAKUT were included. Data on demographics, maternal history, and specific types of anomalies were collected and analyzed. Results: The study found a prevalence of 11.3% for CAKUT among all urology cases attended. Demographically, the cohort was predominantly male (65%), with a notable finding that 66% of patients received their first diagnosis after the age of 20 years. Maternal history revealed a high rate of oligohydramnios (35%) in index pregnancies. The most frequent anomalies were hydronephrosis (77%) and ureteropelvic junction (UPJ) obstruction (66%), with some patients presenting with multiple anomalies concurrently. Conclusion: The findings suggest that CAKUT constitutes a significant disease burden in the study population. The high proportion of patients diagnosed in adulthood underscores a critical need for enhanced prenatal and postnatal screening programs. Timely detection and intervention are crucial to mitigate the progression of these conditions and improve long-term renal outcomes in Bangladesh. Ibrahim Card Med J 2024; 14 (2): 26-31